ASHRAE Global Thermal Comfort Database II: Comparison of Thermal Comfort Conditions in Different Type of Building - Roni, Mohammad Safwan Bin; Hariri, Azian (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Thermal acceptability among students and workers in the school and office is essential as it may affect their productivity and performance. Based on ASHRAE Global Thermal Comfort Database II, there is a lot of data related to thermal comfort conditions of different building types, such as classrooms and offices. Still, limited study had been done to compare this thermal comfort acceptability between different kinds of buildings and climate. This study examines and compare the thermal comfort levels of different types of buildings and climate based on data extracted from ASHRAE Global Thermal Comfort Database II. The analysis was done using statistical packages for social science (SPSS) for 200 data related to two types of building (air-conditioning classrooms and air-conditioning office) in two different climates (Monsoon-influenced hot-summer humid continental and hot-summer Mediterranean climates). Data was analyse using descriptive statistics, normality test, correlation, and regression based on four main parameters of predicted mean vote (PMV), air temperature, air velocity, and operative temperature. Most of the data were normally distributed and the coefficient correlation were identified with parametric testing. Based on descriptive statistics, the Monsoon-influenced hot-summer humid continental for the classroom has the lowest range of temperature and PMV which were 17.5℃ to 21.0℃ and range of PMV were -3 to -1 (cold to slightly cool). The optimum temperature for classrooms and offices with Monsoon-influenced hot-summer humid continental is 26.08℃ and 24.81℃ respectively. Meanwhile, for hot-summer Mediterranean was 20.38℃ for classroom and 25.06℃ for office.